Fatty Acid-Binding Protein 3 Expression in the Brain and Skin in Human Synucleinopathies - Oizumi, Hideki; Yamasaki, Kenshi; Suzuki, Hiroyoshi; Hasegawa, Takafumi; Sugimura, Yoko; Baba, Toru; Fukunaga, Kohji; Takeda, Atsushi (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) and multiple system atrophy are types of adult-onset neurodegenerative disorders named synucleinopathies, which are characterized by prominent intracellular α-synuclein (αSyn) aggregates. We have previously found that αSyn aggregates and the vulnerability of dopaminergic neurons in the mouse brain are partly associated with the expression of fatty acid-binding protein 3 (FABP3, heart FABP). However, it remains to be elucidated whether FABP3 accumulation is associated with αSyn aggregates in human tissues. Here, we histologically studied FABP3 expression in human tissues obtained from patients with synucleinopathies, patients with Alzheimer disease (AD) and controls. We found that (1) a variety of neurons expressed the FABP3 protein in human brain tissues, (2) FABP3 was colocalized with αSyn aggregates in the brains of individuals with synucleinopathies but not with amyloid β or p-tau aggregates in the brains of individuals with AD, and (3) FABP3 was not present in p-αSyn deposits in biopsied skin tissues from individuals with PD. These findings suggest that FABP3 expression is associated with αSyn aggregation in synucleinopathies and provide new insights into the involvement of FABP3 in synucleinopathies.